(untitled) (Itinera, 2022)
Some objects and some things that happen are difficult to understand because they escape what one is used to find. When something cannot be explained by custom or the habitual rules of a society, a charitable reaction assumes things nevertheless make sense, but they demand that one finds explanations that may apply to them and therefore explain of the objects under observation. Changes in contexts and places where things are found modify how phenomena are expected to happen; associations, metaphors, and interpretation are some mechanisms of change that displace habits in place. Art ultimately is the suspect when phenomena in our everyday life manifest these changes.